Characterizing the circular RNA landscape in phloem sap of Brassica napus - Kim Lara Lühmann; Zsófia Fekete; Rita Fernandes; Julia Kehr (PLoS ONE, 2026)
In plants, long-distance transport and phloem-mediated signal distribution play crucial roles in regulating stress adaptation and development. Phloem sap contains various types of RNAs, including small RNAs (sRNAs), messenger RNAs (mRNAs), and long noncoding RNAs (lncRNAs). Recently, endogenous circular RNAs have been identified in phloem sap of apple trees. Some phloem RNAs have been shown to have long-distance signaling functions, but for most, no functions have yet been determined. Due to their stability, circRNAs are interesting candidates with potential functions in long-distance signaling. Therefore, we aimed to characterize the circRNA content in the phloem sap of the crop plant Brassica napus . To achieve this, we performed Illumina sequencing of rRNA-depleted, circRNA-enriched, and sRNA libraries. The analysis revealed 1,734 distinct circRNAs in the phloem sap of B. napus . Of these, we validated ten circRNAs by PCR amplification and Sanger sequencing of their back-splicing junctions (BSJs). Using circ-Panel Nanopore sequencing, we investigated the full-length sequences of 14 circRNAs from phloem sap and leaf samples, identifying seven high-confidence candidates that exhibit potential intron retention and isoform variation across the two tissues. The investigation of potential interaction partners from phloem circRNA identified miRNA target sites on multiple circRNAs, particularly for known phloem-mobile miRNAs like miR156, miR169, and miR395. With Microscale Thermophoresis (MST), we were able to show the ability of the abundant RNA-binding protein BnGRP7 to bind the phloem circRNA circBnaANL2(7,8) with a dissociation constant of around 1 µM, raising questions about the involvement of RBPs in circRNA transport, stabilization, and function in phloem sap.